Molecular identification of Phytophthora spp. causing citrus decline in Vidarbha region of Maharashtra - A. INGLE and S. NERKAR, A.K. DAS*, A. KUMAR, (Indian Phytopathology, 2012)
A PCR-based system based on the sequence and restriction digests of the ITS region of the genomic ribosomal RNA gene repeat (rDNA) was used as a tool to characterize fourteen Phytophthora spp. isolates collected from the citrus orchards of Vidarbha region of Maharashtra. The results of RFLP analysis of internal transcribed spacer (ITS) region of ribosomal DNA of all the isolates revealed a difference in their restriction pattern for MspI and AluI digestions. Comparative data of RFLP analysis suggest 12 isolates as Phytophthora nicotianae and the rest two as P. palmivora. These two species were further detected with species-specific primers and sequence analysis of rDNA. The study conclusively revealed that P. nicotianae and P. palmivora are the most prevalent species in citrus orchards of Vidarbha region causing the widespread problem of citrus decline.